Effective utilization questions economic resources - Olim Sabirovich Kazakov; Jasurbek Nematzhonov (Zien Journals, 2022)
In modern conditions on предприятих and the organisations questions of use of available economic resources are got by great value. In article questions of use of economic resources at the enterprises and increases of efficiency of use by these resources are studied. Offers in this direction are developed.
Keywords: The Pandemic; resources; economic resources; technological resources